Physiological Responses of Local Goat Fed by Green Concentrate - Wahyuningsih, Murtry; Naser, Abdullah; Abdullah, Sirajuddin (Universitas Tadulako, 2022)
This research aims to determine the physiological response of local goats fed green concentrates in the form of Indigofera zollingeriana, Sesbania grandiflora and Gliricidiasepium. This research used a Completely Randomized Factorial Design with the first factor being 3 types of nuts and the second factor being 3 treatment levels (60%, 70% and 80%). The results of the study showed that body weight gain and efficiency of forage use for goats fed Gamal Green Concentrate were significantly lower than Turi and Tarum Green concentrates, however consumption of local dry goat content gave the same results. However, based on statistical tests, goats fed green concentrate had no significant effect on the status of goat physiology. The body temperature of local goats given 80% green concentrate was higher compared to 60% green concentrate and 70% green concentrate. The pulse frequency and respiratory frequency of local goats given 60% green concentrate were higher compared to 70% green concentrate and 80% green concentrate. However, based on statistical tests, goats fed green concentrate had no significant effect on the status of goat physiology.